Trzymając telewizyjnego pilota czy ściskając kierownicę roweru? Sposoby spędzania czasu wolnego w przestrzeni miasta późnonowoczesnego n.p. Katowic - Górny, Andrzej (Studia Etnologiczne i Antropologiczne, 2010)
The present time can be defined by means of the epoch of choices. The contemporary reality is amazingly pluralist in all practical dimensions of life. In modern societies we also deal with a particular paradox with respect to time — on the one hand, it is organized according to an objective academic model and, on the other, it splits into different time cultures every day. A new selected sphere of human time, leisure time, undergoes division. What appears are new needs and, at the same time, institutions which satisfy them in a different way: a service, educational and recreational one. The former homogenous human action is being split into many separated and isolated “times”. Considering the issue of free time from the sociological perspective, it is legitimate to assume that ways of spending leisure time are inscribed into fairly visible cultural patterns which within years are subject to dynamics. It is their identification in reference to the social space of Katowice that became the subject matter of the very article. It presents the results of the studies conducted in July and August 2007 on the sample of 492 adult inhabitants of Katowice. In the context of the issues dealt with, several questions arise: How do inhabitants of Katowice use their free time? Do the forms connected with the physical activity or rather passive rest dominate? How much time do they devote to the Internet and television? What is the activeness of the respondents in their free time when it comes to culture? As a predominant analytical perspective served an attempt to answer the question if the changes connected with a more and more common trend on the so called healthy lifestyle or a growing pressure on the creation of the cultural wealth, also affect the ways of spending leisure time. In view of a big social, economic and spacious diversification, the area of Katowice is extremely interesting research area of the very problem among the contemporary inhabitants of a big city.